One new species and two new records of the spider wasp genus Telostholus Haupt, 1929 in China, with a key to the world species - Song, Zhi-Yan; Li, Qiang; Dong, Li-Li; Ma, Li (Zootaxa, 2024)
The taxonomy of the genus Telostholus (Hymenoptera: Pompilidae: Pompilinae) from China is studied and one species is newly described and illustrated: T. venarectus Song & Ma, sp. nov. Additionally, two species, T. lao and T. malayensis are newly reported from China. A key to the world species of Telostholus is provided.